Latvuspeiton maastomittausmenetelmien vertailu - Korhonen, Lauri; Korhonen, Kari T.; Rautiainen, Miina; Stenberg, Pauline (Metsäntutkimuslaitos, 2006)
Seloste artikkelista: Korhonen, L., Korhonen, K.T., Rautiainen, M. & Stenberg, P. 2006. Estimation of forest canopy cover: a comparison of field measurement techniques. Silva Fennica 40(4): 577–588.
Tutkimusseloste